Synthesis and Antibacterial Activity of Alkylamine-Linked Pleuromutilin Derivatives - Kerrin Hainsworth; Melissa M. Cadelis; Florent Rouvier; Jean Michel Brunel; Brent R. Copp (MDPI AG, 2024)
In an effort to expand the spectrum of the antibacterial activity of pleuromutilin, a series of amine- and polyamine-linked analogues were prepared and evaluated for activities against a panel of microorganisms. Simple C-22-substituted amino esters or diamines 16, 17, 18, and 22, as well as two unusual amine-linked bis-pleuromutilin examples 20 and 23, displayed variable levels of activity towards Staphylococcus aureus ATCC 25923 and methicillin-resistant S. aureus, but with no detectable activities towards Gram-negative bacteria. Fortunately, the incorporation of a longer-chain triamine or polyamine (spermine) at C-22 did afford analogues (30, 31) that exhibited activity towards both S. aureus ATCC 25923 and Escherichia coli ATCC 25922 with MIC 6.1-13.4 µM. Spermine-pleuromutilin analogue 31 was also able to enhance the action of doxycycline towards Pseudomonas aeruginosa ATCC 27853 by eight-fold, highlighting it as a useful scaffold for the development of new antibacterial pleuromutilin analogues that exhibit a broader spectrum of activity.